Вплив стилів батьківського виховання на формування життєвих сценаріїв особистості - Сугакова П. В (My University, 2026)
The qualification paper examines the influence of parenting styles on the formation of an individual's life scripts. The study reveals theoretical approaches to parenting and its role in personality development. The characteristics of democratic, authoritarian, permissive, and neglectful parenting styles are analyzed, as well as their impact on the development of autonomy, self-esteem, and emotional wellbeing. The paper highlights the main provisions of the life script concept and determines the significance of the family environment in shaping an individual's life attitudes. An empirical study was conducted involving 100 respondents aged 20 to 40 years. An original questionnaire developed using Google Forms was used for data collection. The results indicate that the democratic parenting style contributes to the development of autonomy, self-confidence, and psychological resilience. At the same time, the authoritarian parenting style is associated with higher levels of anxiety and dependence on external evaluation. Based on the findings, practical recommendations for the formation of adaptive life scripts were developed.
The influence of parenting styles on the formation of personality life scenarios
Keywords: стиль батьківського виховання; життєвий сценарій; особистість; автономність; тривожність; дитинство; сім’я; 053 "Психологія"; parenting style; life script; personality; autonomy; anxiety; childhood; family